Why do some SMEs engage in joint internationalisation and others do not? Exploring the role of mental images in collective international opportunity recognition - Eini Haaja (Springer Nature, 2022)
This study explores the under-researched yet increasingly important process of collective international opportunity recognition. Collective opportunities are created through the interaction and joint acts of several firms and, thus, involve a complex merging of different perspectives and interests. This study analyses why some entrepreneurs recognise collective opportunities in foreign markets while others do not. The empirical data comprise qualitative interviews with 20 representatives of Finnish small- and medium-sized maritime enterprises that are exploring internationalisation opportunities in Norway and Russia. The study suggests that collective international opportunity recognition is affected by the entrepreneur’s mental images of inter-firm collaboration and the foreign market. These images comprise his or her interpretations of relevant experiences, the current strategies and resources, and attractiveness of the context. Mental images are built on information and stimuli that the entrepreneur receives regarding potential partner firms and the foreign market, although these inputs are interpreted through the current images. The study advances international entrepreneurship research by providing insights into the subjective and contextual process of collective international opportunity recognition from the perspective of individual entrepreneurs, exploring mental images as drivers in this process, and describing the content of these images. The study highlights the complexities involved in opportunity recognition in an international collaborative setting.